Student’s Problem in Listening Skill of Vocational High School At Dharma Budi Sidamanik - Julinda Vingki Monika Simbolon; Herna Friska Sihaloho; Bobby Hermanto Doloksaribu; Muhammad Rifai (Ilmu Inovasi Nusantara, 2022)
This article describes the problem faced by students in Listening Skills at Vocational High School level, in particular it discusses (1) problems they face in listening to English and (2) how the teacher solves the problem. This research uses qualitative descriptive, and was conducted at Vocational High School at Dharma Budi Sidamanik, Sidamanik District, Simalungun Regency in class X with 30 students. The findings show (1) students do not have sufficient listening skills, (2) problems faced by students in listening are related to with their level of concentration, the habit of speaking English, limited vocabulary, similarity in pronunciation in English and also the problem of accents, there are several distinctive accents such as British and American, and (3) to overcome these problems, the teacher applies the Community Language Learning method by asking students to make study groups, in learning to listen to English. Thus, it can be concluded that the teacher's efforts are relevant to listening problems faced by students